2017
DOI: 10.5194/bg-14-3971-2017
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and UV light affect the activity of marine cell-free enzymes

Abstract: Abstract. Microbial extracellular enzymatic activity (EEA) is the rate-limiting step in the degradation of organic matter in the oceans. These extracellular enzymes exist in two forms: cell-bound, which are attached to the microbial cell wall, and cell-free, which are completely free of the cell. Contrary to previous understanding, cell-free extracellular enzymes make up a substantial proportion of the total marine EEA. Little is known about these abundant cell-free enzymes, including what factors control thei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…According to the size-reactivity model, microbes selectively degrade high-molecular-weight molecules [74,75], as these compounds are generally too large to be transported across cell membranes [76]. Therefore, microbial extracellular enzymatic activity is the rate-limiting step in the degradation of organic matter in the oceans [77]. Our results, therefore, indicate that persistent MHWs, especially if generating T anomalies above 1.5 • C, can stimulate extracellular enzymatic activities and thus C degradation rates, causing a potential rise in the efficiency of energy transfer to higher trophic levels.…”
Section: Mhws' Effects On Organic C Degradation Ratesmentioning
confidence: 99%
“…According to the size-reactivity model, microbes selectively degrade high-molecular-weight molecules [74,75], as these compounds are generally too large to be transported across cell membranes [76]. Therefore, microbial extracellular enzymatic activity is the rate-limiting step in the degradation of organic matter in the oceans [77]. Our results, therefore, indicate that persistent MHWs, especially if generating T anomalies above 1.5 • C, can stimulate extracellular enzymatic activities and thus C degradation rates, causing a potential rise in the efficiency of energy transfer to higher trophic levels.…”
Section: Mhws' Effects On Organic C Degradation Ratesmentioning
confidence: 99%
“…Thus, the activity of extracellular microbial enzymes is likely the rate-determining step in plant cell lysis. The activity itself increases with increasing enzyme concentration and is sensitive to both temperature and ultraviolet (UV) light exposure 33 . Inside eukaryotic cells are cytoplasmic organelles that contain mitochondrial and chloroplast DNA and consist of a double lipid bilayer membrane and like animal cells, undergo similar lysis processes.…”
Section: Cell and Organelle Lysismentioning
confidence: 99%
“…Interestingly, these authors found a significant effect of UVR on leucine aminopeptidase and alkaline phosphatase but not on beta-glucosidase at any treatment level. A recent study with cell-free enzymes from New Zealand waters revealed that environmentally relevant UVR irradiances reduced cell-free enzyme activities up to 87% in 36 h when compared to dark controls, likely a consequence of photodegradation ( Thomson et al, 2017 ). This study also revealed that the magnitude of the effect of UVR on cell-free enzymes varied depending on the UVR fraction.…”
Section: Fate Of the ‘Living Dead’ Cell-free Eeamentioning
confidence: 99%
“…Interestingly, consistent with the findings from Steen and Arnosti (2011) , the effect of UVR differed depending on the enzyme; significantly decreasing the activity of cell-free leucine aminopeptidase and alkaline phosphatase, but not affecting β-glucosidase. This indicates that UVR (at ambient levels of radiation) can be a key factor reducing the activity (and lifetime) of cell-free enzymes ( Thomson et al, 2017 ). Also, the fact that UVR effects vary among different enzymes indicates that UVR might change the spectrum of the EEA and thereby the composition of the resulting organic matter pool.…”
Section: Fate Of the ‘Living Dead’ Cell-free Eeamentioning
confidence: 99%